ANALISIS KEBUTUHAN DIKLAT (TRAINING NEEDS ANALYSIS) DI INSTITUTO NACIONAL DA ADMINISTRAÃÃO PÃBLICA REPÃBLICA DEMOCRÃTICA DE TIMOR LESTE - , AMANDIO PAULINO GASTAO DO ROSARIO DE SOUSA, Prof. Dr. Warsito Utomo ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research discussed the Training Needs Analysis (TNA) in the Instituto Nacional da Administração Pública (INAP). This aimed to identify the TNA at INAP, from organizational level analysis, job/position level analysis, and individual level analysis. Method adopted in this research involved qualitative approach-based descriptive method, i.e. identifying particular facts, symptoms, or phenomenonâs